Minimization of losses of the budget program at reduction of its financing - Parkhomenko, Pavlo (Social Development and Security, 2020)
One of the problems that arise in the daily practice of management - fund managers in making management decisions is considered. Namely, the need to redistribute appropriations between budget programs and select measures that reduce funding the least will affect the effectiveness of the program and minimize the risks of non-implementation of the program as a whole. To solve the problem, an approach is proposed using a statistical method of quantitative risk analysis based on the definition of two indicators: the probability of losses (losses) in the event of a reduction in program funding and the average and range of these expected losses (losses). An example of using the proposed approach for two possible options for reducing funding for a program between the three potential groups of activities of this program. The mechanism of summary of calculations in the final table acceptable for the analysis and acceptance of the final decision in an instance of management concerning a choice of the least risky variant is offered. It is noted that this approach can be applied in the presence of more than two alternatives to reduce funding for the program and for more than three potential groups of measures selected to reduce funding.